Current perspectives for SARS-CoV-2 vaccination efficacy improvement in patients with active treatment against cancer. (September 2021) - Barrière, Jérôme; Re, Daniel; Peyrade, Frédéric; Carles, Michel
Abstract: A higher risk of death from coronavirus disease 19 has been shown for patients with solid cancers or haematological malignancies (HM). Thanks to the accelerated development of anti–SARS-SoV-2 vaccines in less than a year since the start of the global pandemic, patients with cancer were quickly prioritised in early 2021 for vaccination, however dependent on the very unequal availability at the global level. Impaired immunogenicity of SARS-CoV-2 mRNA vaccines in immunocompromised patients was rapidly reported as early as April 2021, although the vaccination fortunately appears to be generally effective without increasing the spacing. Worryingly, the humoral response of the SARS-CoV-2 vaccination is, however, considered insufficient in patients followed for HM, in particular when they are on anti-CD20 treatment. Thus, improving vaccination coverage by strengthening immune stimulation should be evaluated in patients under active treatment against cancer. Here, we discuss three different approaches: a third dose of early vaccine (repeated immune stimulation), heterologous prime-boost vaccination (multimodal immune stimulation) and a double-dose strategy (maximisation of immune response). Dedicated therapeutic trials, currently almost non-existent, seem rapidly necessary. Highlights: Risks of hospitalisation and death increase for patients with cancer and coronavirus disease 19. Patients with cancer should be prioritised for anti–SARS-CoV-2 vaccination. Humoral response of SARS-CoV-2 mRNA vaccines is impaired in this population. Ways of improving vaccination coverage for dedicated therapeutic trials are discussed.